Urinary Incontinence Awareness and Attitude Scale (Urinas): A Reliability and Validity Study - Avcı, İlknur Aydın; Yildirim, Ozge Oz; Eren, Dilek Celik (Lippincott Williams & Wilkins, 2022)
PURPOSE: This purpose of this study was to develop an instrument, the Urinary Incontinence Awareness and Attitude Scale (URINAS), to measure incontinence awareness and attitude, and to evaluate its reliability and validity. DESIGN: Instrument development and psychometric evaluation. SUBJECTS AND SETTING: The URINAS was validated in a group of individuals cared for at a family health center in Samsun, in northern Turkey. The sample comprised 637 respondents. Nearly three-fourths of participants (74.3%, n = 473) were female; their average age was 30.2 years. More than one-third of participants (35.6%, n = 227) reported urinary incontinence (UI). METHODS: Participants completed a questionnaire designed for the study that queried demographic and pertinent clinical data; they also completed the URINAS and the Urogenital Distress Inventory (UDI-6). Explanatory factor analysis was then performed to evaluate validity of the URNAS. Parallel from reliability was evaluated by comparing URINAS and UDI-6 scores to determine parallel form reliability, and the Cronbach alpha was used to evaluate internal consistency. RESULTS: The URINAS comprises 26 items, divided into 5 subdimensions. The total explanatory variance of the scale is 65.3%, and the factor loadings of the scale items range from 0.38 to 0.85. A significant relationship was found in the correlation analysis between the UDI-6 used for the parallel form and the URINAS. Cronbach alpha coefficients vary from 0.60 and 0.92. CONCLUSIONS: The URINAS is a valid and reliable instrument that can be used for measuring awareness and attitudes toward UI.
Öz Yildirim, Özge/0000-0003-4810-563X; Aydin Avci, Ilknur/0000-0002-5379-3038;
Keywords: Instrument Development; Reliability and Validity; Urinary Incontinence